Internalisasi Nilai-Nilai Karakter Islami Dalam Kegiatan Yasinan Rutin di MAN 2 Deli Serdang - Afiva, Nazwa; Miswar, Miswar (Jayapangus Press, 2025)
Education not only aims to increase knowledge, but also to form noble character and morals. In the context of Islamic education, character formation is a top priority. However, the moral challenges among the younger generation today show that effective methods are needed to inculcate Islamic values in a practical and sustainable manner. This research aims to describe the process of internalizing Islamic character values through routine yasinan activities at MAN 2 Deli Serdang. The cultivation of character values such as religious character, discipline, responsibility, honesty and togetherness is carried out through habituation, teacher example, and consistent supervision. The method used is a descriptive qualitative approach through observation, interviews, and documentation. The data analysis technique was carried out using data reduction, data presentation and conclusion drawn. The results of the study show that yasinan activities are an effective medium in shaping the Islamic character of students. This activity not only strengthens the spiritual aspect, but also forms a positive attitude in the daily lives of students in the school environment and the community. Thus, this routine yasinan activity needs to continue to be carried out and developed as part of a strategic program in fostering the Islamic character of students in a sustainable manner in the educational environment.